Antithrombin supplementation to prevent venous thromboembolism: A case of hereditary antithrombin deficiency with increased antithrombin clearance during pregnancy and peripartum - Ayako Kaneda-Takeuchi; Tomoaki Oda; Mei Kitamoto; Emiyu Fujiwara; Kenta Kawai; Megumi Narumi; Yoshimasa Horikoshi; Masako Matsumoto; Yukiko Kohmura-Kobayashi; Naomi Furuta-Isomura; Toshiyuki Uchida; Kazunao Suzuki; et al. (Thrombosis Update)
Hereditary antithrombin deficiency (HATD) is an autosomal dominant disorder that significantly increases the risk of venous thromboembolism (VTE) during pregnancy. Based on our experience with three previous cases and the Japanese clinical guidelines, we manage high-risk VTE in pregnant women with HATD using unfractionated heparin (UFH) and antithrombin (AT) supplementation from early pregnancy to the peripartum period. Herein, we report another case of HATD type 1 in pregnancy and evaluate changes in AT clearance. A 29-year-old woman had a history of pulmonary embolism (PE) at 14 years and a family history of HATD with AT activity of 47 % at baseline, which decreased to 31 % when she developed PE after an abortion. During her second pregnancy, she was treated with UFH and AT concentrate (ATC) with doses increasing from 50 to 100 IU/kg to achieve target AT activity levels of 50–60 % throughout pregnancy and 70 % during delivery. She delivered a healthy male infant at 39 weeks of gestation. She started to take warfarin on postpartum day 1, with an uneventful postpartum course. AT clearance, calculated using plasma AT antigen levels, showed notable increases in the first and late third trimesters, peaking around delivery and coinciding with elevated thrombin-antithrombin complex levels. These findings suggest increased AT consumption during these periods, which may contribute to unexpected decreases in AT activity. We propose close monitoring of AT activity and providing adequate ATC supplementation alongside anticoagulation throughout pregnancy, particularly during periods of elevated AT clearance, to minimize VTE risks in HATD patients.